Peran Muhammadiyah Dalam Upaya Pengembangan Pendidikan Holistik di Indonesia - Bimba Valid Fathony; Fadhlan Ramadhani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2025)
Holistic education plays a crucial role in the face of today's digital era. This approach in the education sector is rooted in the idea that individuals can fundamentally find their identity, meaning, and purpose in life through their interactions with the community, nature, and spiritual principles. Muhammadiyah's Holistic Education is an educational paradigm that unites intellectual, professional, and Islamic principles in a comprehensive and integrated manner. This educational model not only focuses on the cognitive dimension (knowledge), but also seeks to hone the affective (attitudes and values) and psychomotor (practical and physical skills) dimensions of students in a balanced manner. This study uses a qualitative library research method where this research uses data from literature or written materials available in the library, such as books, journals, documents, and other written works. The results of this study explain that, Overall, Muhammadiyah plays a central role in advancing holistic education in Indonesia by uniting Islamic values, modern science, and character in a comprehensive, innovative, and sustainable education system. Muhammadiyah is a pioneer of holistic education in Indonesia with a significant impact on the development of quality and high-moral human resources for Indonesia.